Female Peacekeepers: UNSC Resolution 1325 and the Persistence of Gender Stereotypes in the Chilean Armed Forces. Issue 1 (1st January 2021) - Jenne, Nicole; Ulloa Bisshopp, Fiorella
ABSTRACT: In 2000, the United Nations Security Council Resolution 1325 on Women, Peace and Security recognized an urgent need to mainstream a gender perspective into peacekeeping operations in order to achieve gender equality. UN member states have been called upon to implement the Resolution through National Action Plans. Almost two decades after its adoption, research indicates that progress towards the goals set in Resolution 1325 has been slow. This article builds on the case of the Chilean military to assess whether and to what extent a gender perspective has been incorporated into the country's peacekeeping practice. We argue that gender stereotypes have persisted despite Chile's status as a regional pioneer in promoting gender equality in its defence policy. Paradoxically, the new opportunities peacekeeping offered for women in the military have been legitimized by a discourse that conforms to traditional gender stereotypes, such that women serve as the 'peaceful and friendly face' in peacekeeping.